Photocatalyzed elaboration of antibody-based bioconjugates - Le Stum, Marine; Romero, Eugénie; Molander, Gary A. (Beilstein Journal of Organic Chemistry, 2025)
Antibody–drug conjugates (ADCs) represent a promising class of targeted therapeutics, combining the specificity of antibodies with the potency of cytotoxic drugs to enhance therapeutic efficacy while minimizing off-target effects. The development of new chemical methods for bioconjugation is essential to generate ADCs and to optimize their stability, efficacy, and safety. Traditional conjugation methods often face challenges related to site-selectivity and heterogeneous product mixtures, highlighting the need to develop new, innovative chemical strategies. Photoredox chemistry emerges as a powerful tool in this context, enabling precise, mild, and selective modifications of peptides and proteins. By harnessing light to drive chemical transformations, photoredox techniques can facilitate the synthesis of antibody bioconjugates. This perspective will discuss the drive to develop and empower photoredox methods applied to antibody functionalization.
Keywords: antibodies; bioconjugation; bioorthogonality; chemoselectivity; late-stage functionalization; photochemistry